The Reality of Violence Against Wives: Dynamics of Social Settlement and Support in Lamongan, East Java - Sabri, Fahruddin Ali; Rohmah, Linda Farihatur; Ghufron, Muhammad; Hadi, Mukhammad Nur; Musafa'ah, Suqiyah; Nadhifah, Nurul Asiya (Mazahib, 2024)
As a hidden crime, violence against wives is considered a disgrace to be discussed in public, especially reported to state and non-state actors. At first, victims feel able to resolve violence without outside intervention from outside their household, but repetition after repetition of violence requires them to choose what kind of resolution is right for them. This choice should be made after they have the support of individuals in their social environment. This study aims to explore the knowledge and experience of victims of violence against wives in choosing one among legal norms favorable to them. This study uses a critical realist approach by collecting qualitative data with dialogue techniques and observations of three women who were victims and six people who provided support to victims. We conclude that victims experience a dynamic psychological state, where initially, they always try to maintain the integrity of their household. The dominance of men and the subordination of women as a reality of cultural norms are essential factors in choosing ways of resolving conflicts at the community level, and we consider that the community has succeeded in providing social support to victims so that victims feel they get help and defense. However, we hope that this social support can be carried out through structured, systematic, and massive protection of victims of violence from State and non-state actors while considering the cultural norms of the community and supporting the identification of violence.